2009
DOI: 10.1371/journal.pone.0006904
|View full text |Cite|
|
Sign up to set email alerts
|

Intracellular Calcium Deficits in Drosophila Cholinergic Neurons Expressing Wild Type or FAD-Mutant Presenilin

Abstract: Much of our current understanding about neurodegenerative diseases can be attributed to the study of inherited forms of these disorders. For example, mutations in the presenilin 1 and 2 genes have been linked to early onset familial forms of Alzheimer's disease (FAD). Using the Drosophila central nervous system as a model we have investigated the role of presenilin in one of the earliest cellular defects associated with Alzheimer's disease, intracellular calcium deregulation. We show that expression of either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 54 publications
2
11
1
Order By: Relevance
“…Although there exists evidence in favour of FAD-PS mediated ‘ER calcium overload’ theory [ 37 ], the results presented here and several other studies show that the FAD-PS and to a lesser extent wild type PS lead to either attenuated or unchanged ER calcium [ 15 , 16 , 21 , 23 , 25 , 38 41 ]. The reason behind such discrepancies is not completely clear.…”
Section: Discussioncontrasting
confidence: 48%
“…Although there exists evidence in favour of FAD-PS mediated ‘ER calcium overload’ theory [ 37 ], the results presented here and several other studies show that the FAD-PS and to a lesser extent wild type PS lead to either attenuated or unchanged ER calcium [ 15 , 16 , 21 , 23 , 25 , 38 41 ]. The reason behind such discrepancies is not completely clear.…”
Section: Discussioncontrasting
confidence: 48%
“…The neurogenesis and gliogenesis defects caused by PS1 deficiency also make primary cortical neurons derived from PS1 germline knockout embryos quite unsuitable for the study of PS1 function in the regulation of calcium homeostasis. Interestingly, genetic analysis in Drosophila showed that expression of FAD-linked mutant presenilin affects intracellular calcium stores and a loss of function mutant in calmodulin, an effector of intracellular calcium, can suppress presenilin-induced calcium deficits [57]. …”
Section: Presenilins In Calcium Homeostasismentioning
confidence: 99%
“…A DPS-null mutation has been reported to impair learning and memory, which, however, cannot be exclusively attributed to loss-of-function in the Notch pathway (26). In addition, DPS is also required for calcium homeostasis, the disruption of which may lead to cognitive deficits (27)(28)(29). Similarly to investigations in invertebrates, Notch has also been confirmed to interact with PSs and APP in mammals (30,31) and the expression of Notch 1 is increased in the brains of patients with AD (32).…”
Section: Introductionmentioning
confidence: 99%